Releasing pollutants in the soil depth under the conditions of irrigation with municipal wastewater in different situations - Ahmed Hussain; Zahraa Salam Obaid; Ali Abdul Kadhim Ruhaima; Kadhum Al-Majdi; Asal Faiz Hameed; Pradeep Sivaraman; Ahmed S. Abed (Caspian Journal of Environmental Sciences)
Due to the enormous amount of wastewater produced due to urbanization and industrialization, as well as the health and environmental risks associated with wastewater, it is essential to estimate the number of pollutants it generates accurately. This study aims to determine the rate (%) of all types of pollutants in wastewater transferred from the soil. The experiment utilized 16 polyethylene columns with a height of 200 cm and an inner diameter of 15 cm. Six 7-day intermittent flooding experiments were conducted. Three times every 21 days, a continuous and intermittent flooding method was used to dispose wastewater. Magnesium exhibited the highest transfer rate (%) among cations (73.46%), while sodium the lowest (39.76). Chlorine displayed the highest transfer rate among anions (60.85%), while bicarbonate the lowest (32.12%). In the cases of other pollutants, nickel revealed the highest (72.19%), while phosphorus the lowest (2.82%), indicating that the soil can retain phosphorus. In conclusion, examining various methods and comparing the results, plays a significant role in achieving optimal methods and estimating more accurate results.